Pendampingan Digital Marketing sebagai Strategi Pemasaran Produk UMKM di Desa Bandilan Kecamatan Prajekan Kabupaten Bondowoso - Qurrota A’yun; Nadiva Dwi Anatasya; Muhammad Imron Rosyadi; Retno Purwaningsih Saptoulan; Arina Manasikana; Hilmalita Ulul Azmila; Koyun Lailatul Robitoh; Hesti Valentina Febbiyani; Muhammad Rafi Kurniawan; Sabdaprana Dewa (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Digital marketing digitization has become one of the alternatives to increase the sales of Micro, Small, and Medium Enterprises (MSMEs) products. One of the limitations in implementing digital marketing is the lack of skills and knowledge among MSME players in marketing matters. This issue is addressed through the implementation of a digital marketing assistance program focused on MSMEs in Bandilan Village, Prajekan District, Bondowoso Regency. The program targets businesses involved in knitting crafts and cassava chip production. The assistance activities include sharing sessions, creating social media and marketplace accounts, providing training on social media content creation, and direct implementation of digital marketing by the MSME players. The digital marketing platforms utilized in this program are Instagram Business, WhatsApp Business, and Shopee. The benefits of this program are twofold: it increases the sales opportunities for MSME products and also helps the MSME players improve and expand their businesses. This program serves as an alternative and sustainable solution to assist MSME players.